Acousto-optic light modulation : Acousto-optic modulators of high-power laser radiation on the basis of KGW and KYW crystals. (31st October 2020) - Mazur, M M; Mazur, L I; Sirotkin, A A; Ryabinin, A V; Shorin, V N
Abstract: Different modifications of acousto-optic modulators (AOMs) based on KG(WO4 )2 (KGW) and KY(WO4 )2 (KYW) crystals, designed for Q switching of high-power pulsed lasers, is developed and investigated. It is shown that AOMs based on these crystals are universal, can be combined with different lasers in the wavelength range of 1–3 mm, and have a high radiation resistance in the absence of antireflection coatings and light input at Brewster's angle. The operation efficiency of KGW-based AOMs is experimentally demonstrated. Solid-state lasers based on Cr : Er : YSGG (λ = 2.78 μm), Cr : Yb : Ho : YSGG (λ = 2.87 μm), Cr : Tm : Ho : YSGG (λ = 2.09 μm), and Nd : YAG (λ = 1.064 μm) crystals with active acousto-optic Q switching, operating in the repetitively pulsed regime with a high beam quality and without surface destruction, are investigated. Lasing pulses (30–60)-ns long with energy up to 32 mJ at a repetition rate from 1 to 1000 Hz are obtained.